ELASTOMERS USED IN SUGAR INDUSTRY: STUDY OF VULCANIZATION SYSTEM - González Carbonell, Raide Alfonso; Abreu González, Kirenia; Álvarez García, Emilio; Moya Rodríguez, Jorge Laureano (Centro Azúcar Journal, 2009)
This work deals with the study of the vulcanization system of elastomers of general uses in the sugar industry; to determinate the influence of variation of acelerants and activators contain on the mechanical properties of the compound, and formulation cost. The vulcanization system additives studied were the commonly used accelerants: 2-mercaptobenzothiazoline (MBT) and tetrametil thiuram TMTD, and the zinc oxide (ZnO) as a classic activator.